Agglutination Activity of Fasciola gigantica DM9-1, a Mannose-Binding Lectin - Phadungsil, Wansika (Korean J Parasitol, 2021)
The DM9 domain is a protein unit of 60–75 amino acids that has been first detected in the fruit fly Drosophila as a repeated motif of unknown function. Recent research on proteins carrying DM9 domains in the mosquito Anopheles gambiae and the oyster Crassostrea gigas indicated an association with the uptake of microbial organisms. Likewise, in the trematode Fasciola gigantica DM9-1 showed intracellular relocalization following microbial, heat and drug stress. In the present research, we show that FgDM9-1 is a lectin with a novel mannose-binding site that has been recently described for the protein CGL1 of Crassostrea gigas. This property allowed FgDM9-1 to agglutinate gram-positive and -negative bacteria with appropriate cell surface glycosylation patterns. Furthermore, FgDM9-1 caused hemagglutination across all ABO blood group phenotypes. It is speculated that the parenchymal located FgDM9-1 has a role in cellular processes that involve the transport of mannose-carrying molecules in the parenchymal cells of the parasite.